Repurchase Intention on Stellar Dust Lip Stain Timephoria Products as an Impact of Influencer Tasya Farasya’s Credibility and Electronic Word of Mouth (E-WOM) on TikTok - Jeny Sukirman; Wawan Hermawan; Roro Arinda Reswanti J. Pratama (Community Engagement and Emergence Journal (CEEJ), 2026)
This study aims to examine the impact of Tasya Farasya's Influencer Credibility and Electronic Word of Mouth (E-WOM) on Repurchase Intention toward Stellar Dust Lip Stain Timephoria products. A quantitative approach with an explanatory survey method was employed involving 155 respondents who had purchased the product and used TikTok. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that Influencer Credibility is perceived as moderately credible, E-WOM as moderately effective, and Repurchase Intention as moderately high. Hypothesis testing reveals that Influencer Credibility has a positive and significant impact on Repurchase Intention. Similarly, E-WOM also has a positive and significant impact on Repurchase Intention. Furthermore, Influencer Credibility and E-WOM simultaneously have a positive and significant impact on Repurchase Intention. These findings suggest that credible influencer reviews and effective consumer-generated information on TikTok can enhance consumers' intentions to repurchase Stellar Dust Lip Stain Timephoria products.